2022
DOI: 10.3171/2022.2.focus21782
|View full text |Cite
|
Sign up to set email alerts
|

The role of frailty in the clinical management of neurofibromatosis type 1: a mixed-effects modeling study using the Nationwide Readmissions Database

Abstract: OBJECTIVE Frailty embodies a state of increased medical vulnerability that is most often secondary to age-associated decline. Recent literature has highlighted the role of frailty and its association with significantly higher rates of morbidity and mortality in patients with CNS neoplasms. There is a paucity of research regarding the effects of frailty as it relates to neurocutaneous disorders, namely, neurofibromatosis type 1 (NF1). In this study, the authors evaluated the role of frailty in patients with NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Hospital identifiers were included as random effects. [26][27][28][29] Model performance was assessed using the area under the curve (AUC) of each ROC curve, acting as a proxy. An AUC of 0.50 indicates a random guess, whereas values exceeding 0.70 are considered acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital identifiers were included as random effects. [26][27][28][29] Model performance was assessed using the area under the curve (AUC) of each ROC curve, acting as a proxy. An AUC of 0.50 indicates a random guess, whereas values exceeding 0.70 are considered acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first of its kind to assess the combined predictive utility of multiple comorbidity indices for cervical spine fusion and extends the evidence relevant to the role of comorbidity indices in predicting surgical outcomes. Comorbidity indices have previously been used to inform surgical resection of cranial tumors such as pituitary adenomas and those associated with neurofibromatosis type I 35,36 . With respect to spinal procedures, a 2021 study by Hersh et al 37 reported that frailty measured by the 5-item frailty index or the metastatic spinal tumor frailty index is more predictive of adverse outcomes in patients with spinal metastases than CCI in a cohort of 322 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity indices have previously been used to inform surgical resection of cranial tumors such as pituitary adenomas and those associated with neurofibromatosis type I. 35,36 With respect to spinal procedures, a 2021 study by Hersh et al 37 reported that frailty measured by the 5-item frailty index or the metastatic spinal tumor frailty index is more predictive of adverse outcomes in patients with spinal metastases than CCI in a cohort of FIGURE 2. ROC plot for prediction of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Similar studies have also been performed to optimize the use of comorbidity indices for neurosurgical resection of cranial tumors, including pituitary tumors and those associated with Neurofibromatosis type 1. 39,40 For neurosurgery of the spine, studies evaluating comorbidity indices are predominantly focused on adult spinal deformity (ASD) correction and surgical interventions for spinal tumors. For example, a 2021 study by Hersh et al 41 found that frailty measured with either 5-item modified frailty index (mFI-5) or metastatic spinal tumor frailty index scores was more predictive of adverse postoperative outcomes in patients with spinal metastases than the more widely used CCI.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Similar studies have also been performed to optimize the use of comorbidity indices for neurosurgical resection of cranial tumors, including pituitary tumors and those associated with Neurofibromatosis type 1. 39,40…”
Section: Discussionmentioning
confidence: 99%